Construction of Reporter Phage T4::Nluc and Its Application in the Detection of Escherichia coli in Urinary Tract Infections - Zhiyun Hao; Minwei Li; Qiang Zhao; Liye Wang; Ting Liu; Chi Wang; Chengbin Wang (iLabmed)
ABSTRACT Background Urinary tract infections (UTIs) are one of the most common infectious diseases worldwide, predominantly caused by Escherichia coli. We constructed a reporter phage T4::Nluc to achieve rapid, sensitive, and specific detection of Escherichia coli in UTIs. Methods T4::Nluc was constructed using the CRISPR/Cas9 system combined with homologous recombination and was confirmed through Sanger sequencing. The biological properties of T4 and T4::Nluc were compared. Time‐luminescence curves were detected to investigate the limit of detection (LOD) and the influence of urine. Additionally, the specificity of T4::Nluc was examined by co‐culturing it with other pathogens. In total, 104 urinary Escherichia coli isolates were collected to assess detection coverage. Finally, 698 urine samples were collected for clinical validation. Results T4::Nluc was confirmed to be correct. The one‐step growth curves of T4 and T4::Nluc were similar, but the optimal multiplicity of infection for T4 was 1, and that for T4::Nluc was 0.1, indicating that genetic modification had some effect. The LOD was 104 colony‐forming unit/mL detected at 220 min. Urine did not affect detection and T4::Nluc did not cross‐react with other pathogens. T4::Nluc could detect 38.46% of clinical strains, demonstrating higher sensitivity than the double‐layer overlay assay (25.96%). In clinical urine samples, its detection sensitivity was 36.59%, and the specificity was 100%. Conclusion T4::Nluc was successfully constructed and could detect Escherichia coli with superior sensitivity and specificity compared with traditional diagnostics, fulfilling the diagnostic criteria for UTIs while significantly reducing the detection time. This presented a novel approach for rapid and accurate detection of E. coli in UTIs.